RHEUMATOID ARTHRITIS IN THE RUSSIAN FEDERATION ACCORDING TO RUSSIAN ARTHRITIS REGISTRY DATA (COMMUNICATION I) - E. L. Nasonov; D. E. Karateev; A. M. Satybaldyev; E. L. Luchikhina; G. V. Lukina; M. V. Nikolenko; V. A. Bilinskaya; M. E. Dmitrieva; L. A. Bogoderova; N. A. Lapkina; N. V. Chichasova; V. N. Sorotskaya; et al. (Научно-практическая ревматология)
The paper presents the materials of the Russian Arthritis Registry (OREL) that includes 3276 patients from 11 Russian Federation's largest research-and-practical centers situated in Moscow, Saint Petersburg, Novosibirsk, Kazan, Tula, Yaroslavl, Tyumen. It discusses the main goals of setting up registries, compares the results of an analysis of the data available in the Russian Registry OREL and registries of European countries and the USA. The findings suggest that there is non-uniform information on clinical, laboratory, and instrumental parameters in the national registers of a number of European countries and the USA. According to its basic characteristics, the Russian Registry OREL compares favorably with a number of other registries in the completeness of data collection, which allows a general idea of rheumatoidarthritis (RA) patients in Russia. For further development of the OREL Registry, it is necessary to concentrate our attention on the following main areas: to improve the quality of filling out documents; to follow-up patients receiving different RA therapy regimens according to the guidelines of the Association of Rheumatologists of Russia for the treatment of RA; to conduct in-depth studies of comorbidity, primarily depressive disorders; to analyze adverse reactions that make RA therapy difficult; to actively use modules for patients' self-rating of their condition; to develop nursing care, etc.